Taloudellisen tilanteen ja voimavaratekijöiden yhteys elämänlaatuun iäkkäillä ihmisillä. - Ryytty-Tuominen, Kirsti (2024)
Older people themselves evaluate the components of a good quality of life as e.g. health, functional capacity, mental well-being, financial situation and social relationships. Many life changes as you get older require new choices regarding goals and ways of doing things in order to maintain quality of life. The financial situation may limit the possibilities of choices. The purpose of this master's thesis was to find out the association between the financial situation and the quality of life. Physical ability to function, resilience and frequency of meeting social contacts were studied as resource factors. The second question was to find out whether the perceived economic situation affects the association of resource factors and the quality of life.